Hubungan Antara Kinerja Lingkungan Dan Kinerja Komite Audit Dengan Kualitas Pengungkapan Corporate Social Responsibility (Pada Perusahaan Mamufaktur di BEI) - Ivana Siregar; . Lindrianasari; . Komarudin (Universitas Bandar Lampung (UBL), 2013)
This research is aiming investigated the relationship between environmental performance with the quality of corporate social responsibily disclosure, the relationship between audit commitee performance with environmental performance, and the relationship between audit commitee performance Â with the quality of corporate social responsibily disclosure. Environmental performance is measured by ISO 14001 certificate. The proxy of audit commitee performance are audit commitee meeting, audit commitee report, audit charter. The quality of corporate social responsibily disclosure is measured by CSR index from Global Reporting Initiative. The number of samples used in this research were one hundred thirteen manufacturing company. The sampling method used Â purposive sampling method. Data are taken from annual report 2010-2011 of the manufacture companies listed on Indonesia Stock Exchange. The examined technique hypothesis is mutiple regression by using SPSS program. The Â result showed that environmental performance has a positif significant relationship with the quality of Corpoate Social Responsibility disclosure as the first hypothesis. The second hypothesis showed that environmental performance has a positif and sgnificant relationship with audit commitee performance. The third hypothesis showed that audit commitee performance has a positif and sgnificant relationship with the quality of Corpoate Social Responsibility disclosure.